(untitled) (Experimental biology, 2016)
Hybridization of wheat is examined in the article, as a donor of resistance to cold for crossing attracted mainly, less productive, but high-winter-proof sorts of wheat. And also hybridization is a basic method allowing to increase the inherited changeability in populations.